Linux For Dummies, 6th Edition - Dee-Ann LeBlanc (Wiley Publishing, 2011)
* From installing Linux to using it as a desktop operating system, this updated edition gets new users up to speed fast in the nonintimidating For Dummies style * Lets beginning desktop users explore the top Linux distributions * This edition focuses on six of the most popular Linux distributions: Fedora Core, SUSE, Mandrake, Xandros, Linspire (formerly Lindows), and Knoppix * Thoroughly explains installing Fedora Core-the most popular distribution-in addition to each of the other distributions * Covers prepping a computer for Linux, connecting to the Internet, surfing the Web, using cool Internet tools, and manipulating files and directories * The DVD features the latest edition of the Fedora Core distribution, including the source code, as well as Knoppix